Pengaruh Kualitas Produk, Harga, Promosi dan Citra Merek terhadap Keputusan Pembelian Pakaian Wanita di Online Shop - Prasetya, Prasintia; Sugiharto, Totok (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The advancement in technology has led to economic development and transformed the business world on the internet. Due to the growing prevalence of the internet and its easy accessibility, sellers have seized the opportunity to engage in online sales, commonly known as online shopping. This research aims to examine and analyze the influence of product quality, price, promotion, and brand image on the purchasing decisions of women's clothing in online shops. This study utilizes a modified research model from previous studies, with the expectation of providing empirical research results regarding purchasing decisions. Primary data for this study were collected from 153 respondents, women's clothing consumers in Jabodetabek, who made purchases from online shops within the last year. The study employed purposive sampling techniques. Statistical analysis was conducted using the SPSS software, employing multiple linear regression analysis. The research findings indicate that product quality, partially, has a positive influence on purchasing decisions. Price, partially, does not have a positive impact on purchasing decisions. Promotion, partially, has a positive influence on purchasing decisions. Brand image, partially, has a positive impact on purchasing decisions. Furthermore, product quality, price, promotion, and brand image, collectively, have a positive influence on purchasing decisions. It is hoped that this model can also be utilized by women's clothing businesses in online shops to formulate marketing strategies to enhance consumer purchasing decisions.